PENGARUH PENERAPAN STRATEGI PEMBELAJARAN AKTIF TIPE GUIDED NOTE TAKING (GNT) TERHADAP PEMAHAMAN KONSEP METEMATIS SISWA KELAS VII SMPN 28 PADANG - Wulandari, Merry; Zulfaneti, Zulfaneti; Suryani, Mulia (Pendidikan Matematika, 2013)
This research was conducted based on the phenonema indicating that the students understanding of mathematical concept have still low, that can be seen from the completion percentage of I-semester point of VII-grade students of SMPN 28 Padang. This was because the students do not concern with learning. The purpose of this research is to know whether the student understanding of mathematical concept by using the active learning strategy with Guided Note Taking (GNT) type was better than the student understanding of mathematical concept by applying the conventional one of VII-grade students of SMPN 28 Padang. This was experimental research. The population in this research the VII-grade students of SMPN 28 Padang of the year 2013/2014, and they consist of seven classes with random sampling technique. The selected classes are VII.8 class as an experimental class and VII.5 class as a control. The instruments used in this research was final tests. The form of tests provided was essay with the number of 8 problems with reliability of 0.918. From the results of hypothesis analysis, it is obtained that P-value is 0.001 so that the hypothesis is accepted on the real level of α = 0.05. It can be summarized that the students understanding of mathematical concept by applying the active learning strategy with Guided Note Taking (GNT) type was better than that by using the conventional one for the VII-grade students of SMPN 28 Padang.